Establishing an MRI-Based Protocol and Atlas of the Bearded Dragon (Pogona vitticeps) Brain - Foss, Kari D.; Keller, Krista A.; Kehoe, Spencer P.; Sutton, Bradley P. (Frontiers in Veterinary Science, 2022)
The bearded dragon (Pogona vitticeps) has become a popular companion lizard, and as such, clients have increasingly come to expect the application of advanced diagnostic and therapeutic options in their care. The purpose of this study was to establish an MRI-based protocol and brain atlas to improve diagnostic capabilities in bearded dragons presenting with neurologic dysfunction. Using a high-field 3T magnet, in vivo MRI of the brain was successfully performed in 7 healthy bearded dragons utilizing an injectable anesthetic protocol utilizing intravenous alfaxalone. From this, we created an atlas of the brain in 3 planes, identifying 9 regions of interest. A total scan time of 35 minutes allowed for the collection of a quality diagnostic scan and all lizards recovered without complication. This study provides practitioners a neuroanatomic reference when performing brain MRI on the bearded dragon along with a concise and rapid MRI protocol.